Disciplining judges : contemporary challenges and controversies - Devlin, Richard F. 1960-; Wildeman, Sheila (Edward Elgar Publishing, 2021)
"Globally, countries are faced with a complex act of statecraft: how to design and defensible complaints and discipline regime. In this collection, contributors provide critical analyses of judicial complaints and discipline systems in thirteen diverse jurisdictions, revealing that an effective and legitimate regime requires the nuanced calibration of numerous public values including independence, accountability, impartiality, fairness, reasoned justification, transparency, representation, and efficiency. The jurisdictions examined are Australia, Canada, China, Croatia, England and Wales, India, Italy, Japan, the Netherlands, Nigeria, Poland, South Africa, and the United States. The core findings are four-fold. First, the norms and practices of each discipline regime differ in ways that reflect distinct social, political, and cultural contexts. Second, some jurisdictions are doing better than others in responding to challenges of designing a nuanced and normatively defensible regime. Third, no jurisdiction has yet managed to construct a regime that can be said to adequately promote public confidence. Finally, important lessons can be learned through analysis of, and critically constructive engagement with, other jurisdictions. The first comprehensive comparative collection on judicial discipline systems, Disciplining Judges, will inspire new conversations among academics, students, judges, governmental officials and political scientists"--